Brace Compliance, Sex, and Initial Cobb Angle as Predictors of Immediate In-Brace Curve Correction in Adolescents With Scheuermann's Kyphosis. Issue 3 (July 2020) - Babaee, Taher; Kamyab, Mojtaba; Sanjari, Mohammad Ali; Ahmadi, Amir; Ganjavian, Mohammad Saleh
ABSTRACT: INTRODUCTION: Bracing is the most effective nonoperative treatment for adolescents with Scheuermann's kyphosis; however, its outcome is not equal for all patients. The effects of potential predictive parameters for the outcome of bracing have not been well evaluated in the literature. The aim of the study was to investigate the potential prognostic factors that affect in-brace curve correction in adolescents with Scheuermann's kyphosis. MATERIALS AND METHODS: In this prospective cohort study, patients with thoracic Scheuermann's kyphosis treated with the Milwaukee brace with a curve of 55° to 86° were included. The primary prognostic factors for in-brace curve correction, including brace compliance and daily exercise by log book, pad pressure by a modified sphygmomanometer, joint hypermobility by Beighton's scale, patients' sex, and initial Cobb angle were measured. Analyses considered multiple linear regression and independent sample t -test. RESULTS: Nineteen boys (13.74 ± 1.55 years) and 33 girls (13.67 ± 1.61 years) were included in the study. The results of the multiple linear regression analysis showed that the degrees of in-brace curve correction were significantly associated with brace compliance and initial Cobb angle ( R 2 = 0.48). The results of the independent t -test showed a significant difference in average curve correction, brace compliance, and in-brace pressure between girls and boys. CONCLUSIONS: Results of the current study indicated that the amount of in-brace curve correction is primarily affected by brace compliance and initial Cobb angle. Brace compliance, curve correction, and pad pressure in boys were significantly higher than in girls.